PENGAMBILAN KEPUTUSAN "MENGERJAKAN SENDIRI" ATAU "SUBKONTRAK" PADA PELAKSANAAN PROYEK DENGAN PENERAPAN MODEL MULTIKRITERIA - Akhmad Mulyadi; Udisubakti Ciptomulyono (Jurnal Teknobisnis, 2006)
The Project Management and Service Department of PT Boma Bisma Indra (BBI-MPJ) encounters numerous civil works in building a Crude Palm Oil (CPO) Refinery Plant. A decision involving many factor has to be made between "in-house construction " or "subcontracting". A multiple criteria decision model involving Analytical Hierarchy Process (AHP) in conjunction with Utility Function was employed in this study to solve the problem of choosing the best alternative. This model was used to optimisefour objectives, i.e. maximizing Strategic Competitive Performance, Managerial Performance, Financial Performance and minimizing Risk. The results obtained indicated that all the civil works should be subcontracted. Civil works for Machinery Foundation was contracted to Subcontractor SA2, and Ancillary Building to Subcontractor SB2; while mechanical works Steel Structure and Platform (Threshing and Pressing Station), Steel.Structure and Platform Lot 7 and Steel Structure and Platform Lot 5 were contracted to Subcontractors M42, MBI, and MC2 respectively.